Feeding behaviour and reproductive biology of the shrimp scad Alepes djedaba (Forsskal, 1775) off Cochin coast, Kerala, south India - Sajana, N.; Bijoy Nandan, S.; Radhakrishnan, C. K. (Indian Journal of Fisheries, 2019)
Food and feeding habits, sex ratio, spawning behaviour, size at first maturity, fecundity and ova diameter of the shrimp scad Alepes djedaba (Forsskal, 1775) exploited off Cochin coast, Kerala are presented in this study. Â A. djedabat is a pelagic carnivore, with a preference for fishes. Low gastrosomatic index (GaSI) values and very low feeding intensity during spawning season indicated poor feeding behaviour during the period.Â The sex ratio did not deviate from the expected 1:1 ratio. Size at first maturity was estimated to be193 mm for male and 174 mm for female. Monthly gonadosomatic index (GSI) values, monthly distribution of gonadal maturation stages and ova diameter revealed that the species had a prolonged breeding season from June to September with a peak in July. Estimated absolute fecundity was 59,744 to 3,30,190 with an average of 1,94,965 eggs. Keywords: Alepes djedaba, Fecundity, Feeding behaviour, Ova diameter, Sex ratio